Serpentine fibulae from Slovenia - Tecco Hvala, Sneža (Arheološki vestnik, 2014)
Fibulae are chronologically sensitive items, and also good indicators of cross-cultural contacts. For this reason, particular attention was and is being paid to them in archaeological studies. This article is also dedicated to them, more precisely to the serpentine fibulae from Slovenia, their typo-chronological framework and distribution. A classification is proposed into seven basic types with further subdivision into variants; and unique examples are also presented. Serpentine fibulae represent the leading form of brooches for fastening clothes worn by both men and women in the sixth century BC. Although their basic form was conceived in the Apennine Peninsula, they quickly spread to neighbouring regions and were further developed by local workshops.